Studi Pola Kecelakaan dan Respons Mitigasi di Ruas Tol Jomo Jawa Timur - Imaduddin Bahtiar Efendi; Radytia Akbar Machfud Dani; Chafid Nur Abdulloh; Abdulah Ahmadi Nejad (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
The Jombang–Mojokerto toll road is a strategic route in East Java supporting logistics distribution and vehicle mobility. However, traffic accident rates on this road remain high, especially in early 2025. This study aims to analyze accident patterns, main causes, and impacts to develop relevant risk mitigation recommendations. A qualitative-descriptive method was used, based on secondary data from credible online media reports. Data were classified into accident patterns, environmental conditions, time of occurrence, and victim impact. Findings show that accidents were mostly caused by collisions between passenger vehicles and trucks in the slow lane, and single-vehicle crashes due to aquaplaning. Key factors include heavy rain, poor drainage, driver fatigue, and low night-time visibility. The most severe impacts came from collisions with heavy vehicles. Recommendations include electronic speed enforcement, safe distance markings, improved drainage, weather alerts, better lighting, and increased patrols. These findings are expected to serve as a reference for improving road safety and reducing future accidents.